Resurrection of the Flesh or Resurrection from the Dead : Implications for Theology - Schmisek, Brian (Book collections on Project MUSE., 2013)
What will our resurrected bodies look like? Will we be young or old? Marked by the physical imperfections of our earthly lives? Does this flesh we carry now rise or is it something other? What does our modern knowledge of the world contribute to our understanding? Brian Schmisek traces developments in the Christian understanding of resurrection, explores the topic in light of biblical data, and mines scientific insights. What results is a synthesis that expresses the essence of the apostolic kerygma in modern terms. Schmisek's impressive combination of solid theological and biblical scholarship with an accessible and welcoming style makes this book an excellent resource for adult education groups, deacon formation classes, undergraduates, and other nonspecialists.